The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1021/acs.jafc.2c02581
|View full text |Cite
|
Sign up to set email alerts
|

Development of Recombinase-Aided Amplification (RAA)-Exo-Probe and RAA-CRISPR/Cas12a Assays for Rapid Detection of Campylobacter jejuni in Food Samples

Abstract: Campylobacter jejuni is the major cause of campylobacteriosis, one of the most common foodborne illnesses worldwide. Here, we report the development of RAA-exo-probe and RAA-CRIPSR/Cas12a assays for the detection of C. jejuni in food samples. The two assays were found to be highly specific to C. jejuni and highly sensitive, as they were one log more sensitive compared to the traditional culture method, with detection thresholds of 9 and 5 copies per reaction, respectively. These assays successfully detected C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…These results confirmed the superior selectivity of our strategy toward MPXV, which is derived from the outstanding specificity of RAA amplification and Cas12a recognition. 47-49…”
Section: Resultsmentioning
confidence: 99%
“…These results confirmed the superior selectivity of our strategy toward MPXV, which is derived from the outstanding specificity of RAA amplification and Cas12a recognition. 47-49…”
Section: Resultsmentioning
confidence: 99%
“…In addition, real-time RT-RAA amplification can also be combined with microfluidic chip technology for multipathogen detection [ 25 ]. In addition, several studies have shown that the combination of RAA technology and the CRISPR system can achieve ultrahigh sensitivity and specific detection of single DNA or RNA molecules [ 26 , 27 , 28 ]. Because RAA technology is specific, sensitive, rapid, and easy to operate, it has great application prospects in the early diagnosis of animal diseases, immediate detection, and import- and export-related quarantine.…”
Section: Discussionmentioning
confidence: 99%
“…The improved specificity of Cas14a makes its usage for ssDNA detection possible without the need for PAM sequence. [30] Campylobacter jejuni Fluorescence Cas12a / / 5 copies / reaction [312] fluorescence, electrochemical, electrochemiluminescence (ECL), and SERS signals) and advanced nanotechnology. Herein, the construction and principle of CRISPR/Cas systemspowered bio/nanosensors will be discussed according to the different signal transduction models.…”
Section: Cas14mentioning
confidence: 99%